Stop Brain Rot! Why We Must Give Narrative Language Priority - Rosemary Sage (Journal of Research in Education and Pedagogy, 2025)
The Oxford University Press (OUP) chose “brain rot” as the 2024 word of the year. Rot means decay or weaken – the latter is more appropriate in this context with a focus on mental deterioration due to technology use limiting higher-level thinking from less face-to-face talk. The British Broadcasting Corporation (BBC, 23.11.24) reported a national study of teenagers who spent between 7-14 hours daily on phones. They were asked to use cutback strategies, like putting phones on silent, leaving them elsewhere if studying or sleeping, and turning off notifications. Participant interviews revealed the benefits of reduction strategies, detailing more direct people contacts to feel happier, less anxious and better able to cope. Direct talking with others led to improved thinking and decision-making, so solving problems more effectively from sharing and refining ideas (Kalk et al, 2024). However, the communication process is marginalised in UK education and rarely fully taught and understood, but regarded as a workplace priority for effective job performance in cosmopolitan settings. Studies show a decline in cognition and appropriate actions dependent on high narrative language levels (R, Sage & L. Sage, 2024). Routine procedures are now implemented by intelligent machines (robots) requiring humans to operate at more complex thinking levels to solve life problems. This article results from a UK teenage pilot study finding that narrative discourse is a daily life-problem resulting from differing multicultural communication styles (Sage, 2024 in press). The introduction defines narrative, with 3 sections discussing the topic: 1) Narrative Discourse and Cognition 2) Information Processing Strategies, and 3) Brain Dominance Implications with a discussion and conclusion.